Up-to-Date Pathologic Classification and Molecular Characteristics of Intrahepatic Cholangiocarcinoma - Chung, Taek; Park, Young Nyun (Frontiers in Medicine, 2022)
Intrahepatic cholangiocarcinoma (iCCA) is an aggressive primary liver malignancy with an increasing incidence worldwide. Recently, histopathologic classification of small duct type and large duct type iCCA has been introduced. Both these types of tumors exhibit differences in clinicopathological features, mutational profiles, and prognosis. Small duct type iCCA is composed of non-mucin-producing cuboidal cells, whereas large duct type iCCA is composed of mucin-producing columnar cells, reflecting different cells of origin. Large duct type iCCA shows more invasive growth and poorer prognosis than small duct type iCCA. The background liver of small duct type iCCA often shows chronic liver disease related to hepatitis B or C viral infection, or alcoholic or non-alcoholic fatty liver disease/steatohepatitis, in contrast to large duct type iCCA that is often related to hepatolithiasis and liver fluke infection. Cholangiolocarcinoma is a variant of small duct type iCCA composed of naïve-looking cuboidal cells forming cords or ductule-like structures, and shows better prognosis than the conventional small duct type. Fibrous tumor stroma, one of the characteristic features of iCCA, contains activated fibroblasts intermixed with innate and adaptive immune cells. The types of stroma (mature versus immature) are related to tumor behavior and prognosis. Low tumor-infiltrating lymphocyte density, KRAS alteration, and chromosomal instability are related to immune-suppressive tumor microenvironments with resistance to PD-1/PD-L1 blockade. Data from recent large-scale exome analyses have revealed the heterogeneity in the molecular profiles of iCCA, showing that small duct type iCCA exhibit frequent BAP1, IDH1/2 hotspot mutations and FGFR2 fusion, in contrast to frequent mutations in KRAS, TP53, and SMAD4 observed in large duct type iCCA. Multi-omics analyses have proposed several molecular classifications of iCCA, including inflammation class and proliferation class. The inflammation class is enriched in inflammatory signaling pathways and expression of cytokines, while the proliferation class has activated oncogenic growth signaling pathways. Diverse pathologic features of iCCA and its associated multi-omics characteristics are currently under active investigation, thereby providing insights into precision therapeutics for patients with iCCA. This review provides the latest knowledge on the histopathologic classification of iCCA and its associated molecular features, ranging from tumor microenvironment to genomic and transcriptomic research.